Comparative Studies of the Gut Microbiota in the Offspring of Mothers With and Without Gestational Diabetes - Crusell, Mie Korslund Wiinblad; Hansen, Tue Haldor; Nielsen, Trine; Allin, Kristine Højgaard; Rühlemann, Malte C.; Damm, Peter; Vestergaard, Henrik; Rørbye, Christina; Jørgensen, Niklas Rye; Christiansen, Ole Bjarne; Heinsen, Femke-Anouska; Franke, Andre; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Background: Offspring of mothers with gestational diabetes mellitus (GDM) have increased risk of developing metabolic disorders as they grow up. Microbial colonization of the newborn gut and environmental exposures affecting the configuration of the gut microbiota during infancy have been linked to increased risk of developing disease during childhood and adulthood. In a convenience sample, we examined whether the intestinal tract of children born to mothers with GDM is differentially colonized in early life compared to offspring of mothers with normal gestational glucose regulation. Secondly, we examined whether any such difference persists during infancy, thus potentially conferring increased risk of developing metabolic disease later in life. Methods: Faecal samples were collected from children of mothers with (n=43) and without GDM (n=82) during the first week of life and again at an average age of 9 months. The gut microbiota was characterized by 16S rRNA gene amplicon sequencing (V1-V2). Differences in diversity and composition according to maternal GDM status were assessed, addressing potential confounding by mode of delivery, perinatal antibiotics treatment, feeding and infant sex. Results: Children of mothers with GDM were featured by a differential composition of the gut microbiota, both during the first week of life and at 9 months, at higher taxonomic and OTU levels. Sixteen and 15 OTUs were differentially abundant after correction for multiple testing during the first week of life and at 9 months, respectively. Two OTUs remained differentially abundant after adjustment for potential confounders both during the first week of life and at 9 months. Richness (OTU) was decreased in neonates born to mothers with GDM; however, at 9 months no difference in richness was observed. There was no difference in Shannon’s diversity or Pielou’s evenness at any timepoint. Longitudinally, we detected differential changes in the gut microbiota composition from birth to infancy according to GDM status. Conclusion: Differences in glycaemic regulation in late pregnancy is linked with relatively modest variation in the gut microbiota composition of the offspring during the first week of life and 9 months after birth.